2023
DOI: 10.1021/acs.biomac.2c01016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physicochemical Properties of Native Mucus and Reconstituted Mucin Gels

Abstract: Simulating native mucus with model systems such as gels made from reconstituted mucin or commercially available polymers presents experimental advantages including greater sample availability and reduced inter- and intradonor heterogeneity. Understanding whether these gels reproduce the complex physical and biochemical properties of native mucus at multiple length scales is critical to building relevant experimental models, but few systematic comparisons have been reported. Here, we compared bulk mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Enzymatic degradation can also be prevented by adding protease inhibitors to the sodium chloride buffer used to solubilize the retrieved mucus. [ 53 ]…”
Section: Current Methods Of Obtaining Mammalian Free‐flowing Mucus An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic degradation can also be prevented by adding protease inhibitors to the sodium chloride buffer used to solubilize the retrieved mucus. [ 53 ]…”
Section: Current Methods Of Obtaining Mammalian Free‐flowing Mucus An...mentioning
confidence: 99%
“…Recently hydrogel properties of native mucus and the reconstituted mucin gels were compared. [ 53a ] Different relevant hydrogel features such as structural, mechanical and biochemical properties were assessed by preparing hydrogels from natively purified, commercial and synthetic mucin and compared with native mucus. [ 53a ] Broadly, reconstituted MUC2 hydrogels exhibited similar material properties (rheology, biochemical properties, transport) compared to native intestinal mucus.…”
Section: Synthetic Mimics Of Mucus and The Mucosal Layermentioning
confidence: 99%
“…Previous work showed that oligosaccharide composition within mucus is altered during CDI, and that C. difficile reduces expression of human MUC2 while preferentially interacting with MUC1 12 . C. difficile also benefits from the cleavage of mucins by specific members of the microbiota 20 There are substantial challenges in obtaining mucus that accurately recapitulates native human mucus in its composition and viscoelasticity 22 , properties likely vital to C. difficile-mucus interactions. Human mucus varies from that of animal models, and the processing of commercial mucins removes important components from native mucus and disrupts its structure 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Protein- and peptide-based hydrogels are desirable biomaterials for biomedical applications because of their inherent biodegradability, the potential to incorporate a vast variety of functions, and their capability to respond to stimuli. Biomedical applications of biological hydrogels include emulating artificial extracellular matrices as scaffolds for tissue engineering, drug delivery by controlled release, biomaterials for wound repair and surgery procedures, biosensors, and imaging. In addition, reconstituted protein-based hydrogels are used to study the function and properties of biological hydrogels such as mucus . Thus, intensive research and bioengineering efforts are currently being directed to design and produce new protein-based hydrogels with tunable mechanical properties and specific functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…6−8 In addition, reconstituted protein-based hydrogels are used to study the function and properties of biological hydrogels such as mucus. 9 Thus, intensive research and bioengineering efforts are currently being directed to design and produce new protein-based hydrogels with tunable mechanical properties and specific functionalities.…”
Section: ■ Introductionmentioning
confidence: 99%